Long-term follow-up and safety of patients after an upfront therapy with Letrozole for early breast cancer in routine clinical care: the PreFace study : GebFra Science = Langfristige Nachbeobachtung und Sicherheit im klinischen Alltag bei Patientinnen nach Upfront-Therapie mit Letrozol zur Behandlung von Brustkrebs im Frühstadium : die PreFace-Studie - Hack, Carolin Christine; Maass, Nicolai; Aktas, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans-Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; Schneeweiss, Andreas; Marmé, Frederik; et al. (Geburtshilfe und Frauenheilkunde, 2024)
Adjuvant treatment of patients with early-stage breast cancer (BC) should include an aromatase inhibitor (AI). Especially patients with a high recurrence risk might benefit from an upfront therapy with an AI for a minimum of five years. Nevertheless, not much is known about the patient selection for this population in clinical practice. Therefore, this study analyzed the prognosis and patient characteristics of postmenopausal patients selected for a five-year upfront letrozole therapy. From 2009 to 2011, 3529 patients were enrolled into the adjuvant phase IV PreFace clinical trial (NCT01908556). Postmenopausal hormone receptor-positive BC patients, for whom an upfront five-year therapy with letrozole (2.5 mg/day) was indicated, were eligible. Disease-free survival (DFS), overall survival (OS) and safety in relation to patient and tumor characteristics were assessed. 3297 patients started letrozole therapy. The majority of patients (n = 1639, 57%) completed the five-year treatment. 34.5% of patients continued with endocrine therapy after the mandated five-year endocrine treatment. Five-year DFS rates were 89% (95% CI: 88-90%) and five-year OS rates were 95% (95% CI: 94-96%). In subgroup analyses, DFS rates were 83%, 84% and 78% for patients with node-positive disease, G3 tumor grading, and pT3 tumors respectively. The main adverse events (any grade) were pain and hot flushes (66.8% and 18.3% of patients). The risk profile of postmenopausal BC patients selected for a five-year upfront letrozole therapy showed a moderate recurrence and death risk. However, in subgroups with unfavorable risk factors, prognosis warrants an improvement, which might be achieved with novel targeted therapies.